Propagation of Kapur Bukit (Dryobalanops beccarii dyer) throught stem cutting and tissue culture - Rebicca, Edward @ May (Universiti Malaysia Sarawak (UNIMAS), 2005)
Kapur bukit (Dryobalanops beccarii Dyer) is a timber species of the Dipterocarpaceae. Kapur bukit is a good source of wood for construction purposes, particularly in plywood production. Vegetative propagation of this species through stem cutting and tissue culture was studied. In the study of vegetative propagation by stem cutting, rooting hormone were used and six treatments included were four different concentrations of indole3- butyric acid (IBA), one with Seradix 2 and water as control. Three trials were conducted and the results showed that this species was difficult to be propagated by cuttings. An untreated cutting from the first trial developed root, shoot and new leaves, no cuttings rooted in second trial, while a cutting that has been treated with 2 gil IBA from the third trial developed root, shoot and new leaf. For surface sterilization, the best regime for all explants was at the 20% 'Clorox' concentration for 15 minutes. The explants were cultured on soft lI:! MS medium incorporated with 10 mill PPM + 10 mill Tetracycline. Best result for callus induction from shoot tips was observed in Y2MS medium supplemented with 1.0 ml PPM + 1.5 mill BAP. New growth of nodal segment was observed in lI:! MS medium supplemented with 1.0 mIll PPM + 1.0 mill BAP. Results from the study showed that further research is required to support these fmdings.